Exact analytical solution of a classical problem of the Josephson tunnel junction - Kuplevakhsky, S.V.; Glukhov, A.M. (Физика низких температур, 2010)
We present the exact and complete analytical solution of the classical problem of the Josephson tunnel junction of arbitrary length W ∈ (0, ∞) in the presence of externally applied magnetic fields and transport currents. Contrary to a wide-spread belief, the exact analytical solution unambiguously proves the absence of any qualitative difference between the so-called «small» (W << 1) and «large» junctions (W >> 1). Another unexpected physical implication of the exact analytical solution is the existence (in the current-carrying state) of unquantized Josephson vortices carrying fractional flux and located near one of the junction's edges. We also refine on the mathematical definition of critical transport current.